IOLite: phase 1b trial of doublet/triplet combinations of dostarlimab with niraparib, carboplatin–paclitaxel, with or without bevacizumab in patients with advanced cancer. Issue 3 (24th March 2022) - Yap, Timothy A; Bessudo, Alberto; Hamilton, Erika; Sachdev, Jasgit; Patel, Manish R; Rodon, Jordi; Evilevitch, Lena; Duncan, Meghan; Guo, Wei; Kumar, Sujatha; Lu, Sharon; Dezube, Bruce J; et al.
Abstract : Background: Doublet combination therapies targeting immune checkpoints have shown promising efficacy in patients with advanced solid tumors, but it is unknown if rational triplet combinations will be well tolerated and associated with improved antitumor activity. The objective of this trial was to determine the recommended phase 2 doses (RP2Ds) and to assess the safety and efficacy of the programmed cell death protein 1 (PD-1) inhibitor dostarlimab in combination with (1) the poly(ADP-ribose) polymerase inhibitor niraparib with or without vascular endothelial growth factor inhibitor bevacizumab or (2) carboplatin–paclitaxel chemotherapy with or without bevacizumab, in patients with advanced cancer. Methods: IOLite is a multicenter, open-label, multi-arm clinical trial. Patients with advanced solid tumors were enrolled. Patients received dostarlimab in combination with niraparib with or without bevacizumab or in combination with carboplatin–paclitaxel with or without bevacizumab until disease progression, unacceptable toxicity, or withdrawal from the study. Prespecified endpoints in all parts were to evaluate the dose-limiting toxicities (DLTs), RP2Ds, pharmacokinetics (PKs), and preliminary efficacy for each combination. Results: A total of 55 patients were enrolled; patients received dostarlimab and: (1) niraparib in part A (n=22); (2) carboplatin–paclitaxel in part B (n=14); (3) niraparib plus bevacizumab in part C (n=13); (4) carboplatin–paclitaxel plus bevacizumab in part D (n=6). The RP2Ds of all combinations were determined. All combinations were safe and tolerable, with no new safety signals observed. DLTs were reported in 2, 1, 2, and 0 patients, in parts A–D, respectively. Preliminary antitumor activity was observed, with confirmed Response Evaluation Criteria in Solid Tumors v1.1 complete/partial responses reported in 4 of 22 patients (18.2%), 6 of 14 patients (42.9%), 4 of 13 patients (30.8%), and 3 of 6 (50.0%) patients, in parts A–D, respectively. Disease control rates were 40.9%, 57.1%, 84.6%, and 83.3%, in parts A–D, respectively. Dostarlimab PK was unaffected by any combinations tested. Coadministration of bevacizumab showed no impact on niraparib PKs. The overall mean PD-1 receptor occupancy was 99.0%. Conclusions: Dostarlimab was well tolerated in both doublet and triplet regimens tested, with promising antitumor activity observed with all combinations. We observed higher disease control rates in the triplet regimens than in doublet regimens. Trial registration number: NCT03307785 .